Efektifitas Permainan Ular Tangga Untuk Meningkatkan Pengetahuan Tentang Bahaya Rokok Pada Siswa SMKS Mathla’un Nawakartika Pandeglang - Dedeh Jubaedah; Ucu Wandi Somantri; E.Egriana Handayani; Siti Nur Ramdaniati; Lambang Satria Himmawan; Dian Nastiti; Heny Sasmita (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2023)
Smoking is one of the main risk factors for several chronic diseases that can lead to death. The negative health effects of smoking are considerable. Education about the dangers of smoking needs to start from school age. Fun educational media can be used to increase students' awareness of the dangers of smoking, one of which is the use of snakes and ladders game media. The purpose of this study was to determine the effect of the use of snakes and ladders game media on increasing knowledge of the dangers of smoking in students of SMKS Mathla'un Nawakartika Pandeglang. This community service approach is delivered through various activities, including site preparation methods, counseling methods, pre and post test methods, and the use of snakes and ladders games about the dangers of smoking. The results of the service showed that students of SMKS Mathla'un Nawakartika had low knowledge and awareness about the dangers of smoking before counseling. After counseling and snake and ladder games have been proven effective in increasing the average knowledge about the dangers of smoking in SMKS Mathla'un Nawakartika students, so that it can be used as an alternative learning media innovation in an effort to increase student knowledge.